Implementation of Discrete Wavelet Transmission for Color Image Transmission in OFDM (International Journal of Engineering and Computer Science, 2014)
Orthogonal frequency division multiplexing technique is most widely used for high speed broadcast purposes & it is  one of the most useful technologies for the present and future wireless communications. The data bits are encoded to multiple sub-carriers using multicarrier modulation technologies when being sent simultaneously  A modified Orthogonal Frequency Division Multiplexing (OFDM) system for robust progressive image transmission is analyzed  .In this paper an image frame is compressed using DWT, and the compressed data is arranged in data vectors ,each with equal no. of coefficients. the simulation results are presented based on bit error rate (BER), the Peak-signal-to-noise ratio (PSNR) over AWGN channel. Based on the simulation outcome, to the color image and different parameter like PSNR,BER,SNR.